Determination of the influence of motor habit in the form of wearing a bag on the formation and persistence of pain complaints of the injured glenohumeral joint - Grzegorz Zieliński; Michał Baszczowski; Aleksandra Byś; Zuzanna Filipiak; Michał Ginszt; Marta Suwała; Piotr Majcher (Journal of Education, Health and Sport, 2019)
INTRODUCTION Pain within the glenohumeral joint is characterized as a limitation and pain when performing shoulder joint movements. Considering that this ailment is found in about 20-33% of the population, it seems to be important to investigate the factors that cause these symptoms. One of the reasons for the formation of pain syndrome may be an incorrect posture and overloading within the glenohumeral joint resulting from the habit of carrying the bag on one arm. AIM OF STUDY The aim of this study was to determine whether the motor habit in the form of wearing a bag is associated with the formation and maintenance of pain within the weighted shoulder joint. MATERIALS AND METHODS Applying the exclusion criteria, 126 women were qualified for the study (mean age 26 years ± 6 years). In order to determine the intensity of pain, the Visual Analogue Scale (VAS) was used. The surveyed women were asked to determine the time of occurrence of the length of pain and to provide anthropometric data such as weight and height. The following were used for statistical analysis: the Shapiro-Wilk test and the Kolmogorov-Smirnov test (with the Lillierfors amendment). Differences were considered statistically significant if the test probability level was lower than the assumed level of significance (p